A contribution to the genus Sphaeroplotina Miyatake (Coleoptera, Coccinellidae, Plotinini) - Tong, Junbo; Chen, Jianjun; Zhang, Xiaoning; Chen, Xiaosheng; Wang, Xingmin (Zootaxa, 2020)
The genus Sphaeroplotina Miyatake, 1969 is reviewed. Sphaeroplotina hainanensis Miyatake, 1969 is redescribed and Sphaeroplotina varimarginata Tong & Wang sp. nov. is described as new to science. Both species are illustrated. A diagnosis of the genus is provided. A key and a distribution map of the known species are also presented.